Human Papillomavirus infection in oral and anogenital sites: prevalence and rates of concordance - Cordeiro, Thaissa Isaias; Silva, Katia Cristina da; Rocha, Willker Menezes da; Lisboa, Daniele Ceperuelo; Passos, Mauro Romero Leal; Gouvea, Tegnus Depes de; Kury, Charbell Miguel; Cavalcanti, Silvia Maria Baeta (Brazilian Journal of Sexually Transmitted Diseases, 2021)
Introduction: HPV infection causes cancer at several anatomical sites. However, the infection’s natural history in non-cervical sites is understudied. Objective: To evaluate oral and anogenital HPV infections, correlating HPV prevalence rates and genotypes with site of infection and risk factors. Methods: In the present study, 351 samples from oral, genital, and anal sites of 117 patients were investigated by using PCR MY09/11 detection, followed by genotyping with RFLP. Results: HPV DNA prevalence was 89.7% (105/117) in genital lesions, 53.8% (63/117) in oral samples, and 58.9% (69/117) in anal samples. Regarding the risk factors associated with HPV in genital lesions, statistically significant rates for oral (p=0.039) and anal sex practices (p=0.0000012) were found. For oral samples, a relevant correlation concerning oral contraceptive use (p=0.039), tobacco smoking (p=0.036), and alcohol use (p=0.0075) were observed; whereas in anal samples, higher risk for HPV infection in patients who reported non-exclusive sexual partners (p=0.013) were found. The presence of viral DNA in all the three sites concurrently was observed in 36.8% of the cases (43/117). Among them, 18% (21/117) presented concordant HPV genotypes, diverging from the literature, and thus corroborating that there is still much to learn about HPV natural history, since different biological behaviors are expected within different populations. Differences in anatomy and physiology of the studied sites can determine different prevalence rates of infection by diverse genotypes. Conclusion: Due to the high prevalence of HPV DNA in extragenital sites, further studies are required to define aspects of HPV natural history among different human anatomical sites.